Latex pipes: sterility of the subjected to the process of sterilization through vapor in "autoclave" - Anders, Patrícia Staciarini (2017)
Among the dentistry and medical articles the tubular dispositive requires special attention to the reprocessing due to lumen cleaning difficulty, and also organic material retention allowing biofilm establishment. The aim of this study was to evaluate the sterility of 30 latex pipes submitted to the sterilization process by vapor in autoclave" in a hospital of Goiania-GO. The latex pipe was cut transversely in 2 pieces of 1cm, one at the extreme(E) and  middle (M).They were inoculated in BHI (Brain Heart Infusion) and incubated at 37ºC for 20 days. The samples with positive growth were seeded on sheep blood agar for microbial isolation. The colonies were characterized by morphology and biochemical tests. Microorganisms were detected in 5 latex pipes samples (16.7%), from these, 3 samples (10%) obtained from middle pieces, and 2 from extreme pieces (6.7%). The contaminants were identified as Gram-positive bacilli (BGP), coagulase negative staphylococcus (ECN), and coagulase positive staphylococcus (ECP). Multiple reprocessed of these articles are distinguished what facilitates to consuming, collapse, drying, formation of cracks, and microorganisms retention. According to our results, the latex pipes reprocess using vapor in autoclave might be a risk to the users.